Design tools for interdisciplinary translation of material experiences. (15th January 2016) - Wilkes, Sarah; Wongsriruksa, Supinya; Howes, Philip; Gamester, Richard; Witchel, Harry; Conreen, Martin; Laughlin, Zoe; Miodownik, Mark
Graphical abstract: Highlights: Material stimuli are vital for designer–materials scientist interactions. We used material stimuli to systematically explore material experiences. Understanding psychophysics allows new material experiences to be developed. An effective approach to designing material experiences combines creativity, scientific evidence and an understanding of cultural resonances. Abstract: Designers increasingly have the opportunity to influence the development of materials as they emerge from the laboratory. In order for this to be successful, designers need to be able to communicate effectively with materials scientists so that materials can be developed with desired functionalities and properties. This paper reviews evidence in favour of using isomorphic sets of material stimuli as tools to bridge the disciplinary gap between designers and materials scientists. We show how these isomorphic sets and their accompanying experiments can be used to translate between the two communities, and to systematically explore the relationship between the technical attributes of materials and subjective experiences of their sound, taste and feel. This paper also explores the limitations of psychophysical approaches and other quantitative techniques for elucidating material experience, and suggests new possibilities for interdisciplinary collaborations that draw on ethnographic approaches.